Perlindungan Terhadap Hak Pendidikan Bagi Anak Yang Berhadapan Dengan Hukum - Dunggio, Syafrudin A.; Ismail, Dian Ekawaty; Mandjo, Julius T. (CV. ITTC INDONESIA, 2022)
Crime can spread to all ages, especially if it is a crime committed at a young age. The juvenile criminal justice system is of particular concern to law enforcement officials, bearing in mind that children in national and international human rights are positioned as a vulnerable group and are given special treatment, and all countries are obliged and have the responsibility to ensure the fulfillment of these special rights is obtained by every child. In connection with this discussion, regarding the guarantee of the right to access education for children in conflict with the law (ABH). As we know, education for every child, including children who are in conflict with the law or living in a correctional institution, is an important thing or can be said to be an investment for children to prepare them for their future. In compiling this paper the author uses the literature study method by examining 21 sources, which include journals, books, and web sites related to the topic of education rights for children in conflict with the law. This paper is intended so that every child, especially for children who are in conflict with the law, gets guarantees for their rights because they have been regulated and are based on clear laws, both national and international laws.